The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/pd.2923
|View full text |Cite
|
Sign up to set email alerts
|

Fetal heart disease and interruption of pregnancy: factors influencing the parental decision‐making process

Abstract: Counselling of parents following the diagnosis of a congenital heart disease should take into account that, in addition of the severity of the congenital heart disease (CHD), ethnicity, gestational age at diagnosis and chromosomal abnormalities influence parental decision regarding pregnancy continuation or interruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 14 publications
5
48
1
2
Order By: Relevance
“…Initially when determining whether to terminate or continue a pregnancy, parents considered the extent of congenital anomalies and the presence of chromosomal abnormalities (Chenni et al, 2012; Menahem and Grimwade, 2003; Rauch et al, 2005; Zyblewski et al, 2009). The severity of the heart defect (Chenni et al, 2012) and the presence of a chromosomal abnormality were associated with proceeding or terminating the pregnancy when a heart defect was identified (Rauch et al, 2005). One study found that the presence of multiple anomalies rather than a single anomaly led parents to terminate a pregnancy because of the more anomalies the increased chance for additional infant morbidity (Rauch et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially when determining whether to terminate or continue a pregnancy, parents considered the extent of congenital anomalies and the presence of chromosomal abnormalities (Chenni et al, 2012; Menahem and Grimwade, 2003; Rauch et al, 2005; Zyblewski et al, 2009). The severity of the heart defect (Chenni et al, 2012) and the presence of a chromosomal abnormality were associated with proceeding or terminating the pregnancy when a heart defect was identified (Rauch et al, 2005). One study found that the presence of multiple anomalies rather than a single anomaly led parents to terminate a pregnancy because of the more anomalies the increased chance for additional infant morbidity (Rauch et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Mothers of premature infants who had secondary education levels were more likely than mothers with primary education to attempt save an infant at ‘all costs’ (Lam et al, 2009). Several other variables were explored in four studies (Chenni et al, 2012; Lam et al, 2009; Rauch et al, 2005; Zyblewski et al, 2009) with mixed results on whether certain demographic characteristics influenced decision-making. Factors that remained inconclusive were maternal age, maternal gravida, maternal parity, race/ethnicity, and gender of the fetus (Chenni et al, 2012; Lam et al, 2009; Rauch et al, 2005; Zyblewski et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Several other pregnancy variables are known to influence the decision to terminate pregnancy, such as maternal age, gravida, parity, gestational age at time of diagnosis, religion and socioeconomic status [16,17,21]. Furthermore, survival rate can be influenced by many other factors [22][23][24], such as term of birth or birth weight.…”
Section: Study Limitationsmentioning
confidence: 97%
“…In the majority of studies, CHDs associated with extracardiac anomalies have worse outcomes [10][11][12][13][14][15]. However, relatively few studies have evaluated the overall effect of known genetic syndromes and major ECMs on pregnancy outcome and mortality in fetal CHD [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…(26) However, study of fetuses with heart disease found that gestational age upon diagnosis was a major factor for the parents to make decision for termination of pregnancy (<0.001). (27) …”
Section: Discussionmentioning
confidence: 99%